Yahwistic Appropriation of Achaemenid Ideology and the Function of Nehemiah 9 in Ezra-Nehemiah - Janzen, David (Journal of Biblical literature, 2017)
The prayer of Neh 9:6-37, and particularly its final two verses, presents the imperial monarchy in a very negative light. This portrayal is far different from the depictions of the Achaemenids found everywhere else in Ezra-Nehemiah, where the Persian kings are great benefactors of the Judean assembly. The presence of this anti-imperial language points to the existence of a group that hoped that God would grant them independence from Persia. In Neh 8-13 as a whole, however, the inclusion of the prayer functions not to promote this view but to present it as terribly misguided. The prayer includes a description of the people that is drawn from Achaemenid ideology, a picture used by the Persian kings to contrast the beneficence bestowed on loyal subjects and the tortures inflicted on the disloyal. Nehemiah 8-13 demonstrates that independence from the Achaemenid king, the figure responsible for sending proper leadership to Judah in order to keep the people faithful to the law, would lead to divine destruction of the community. Here as elsewhere in Ezra-Nehemiah, God permits the continued existence of the assembly only because the figures sent by the king force the people to remain loyal to the law. The best possible life is one under Achaemenid rule, and life without it would be a disaster, which is precisely the claim of Achaemenid imperial ideology.